Non-thermal food engineering operations - Ortega-Rivas, Enrique (Food engineering series, 2012)
This book describes the advent and adaptation of food processing operations, processes and techniques which reduce, even eliminate the thermal component, resulting in microbiologically safe foods with minimum alteration in sensory and nutritive properties